The Empowering Children to Appreciate Javanese Traditional Attire for Cultural Preservation - Pujihartati, Sri Hilmi; Mahendra Wijaya; Sudarsana; Marimin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Currently, the preservation of traditional Javanese clothing faces significant challenges, particularly as children and adolescents are influenced by globalization and modern fashion trends. This influence has also affected traditional attire, which many children wear on formal occasions, shaping their future social status. Through this activity, an effort is made to expose, experiment with, and reflect on one of the most cosmopolitan aspects of cultural heritage—how people dress. This activity is part of a community service program titled Training on the Use of Traditional Javanese Attire for Children, held on Saturday, June 15, 2024, at Sanggar Permadani, Sukoharjo, with 40 participants in attendance. The training was organized by the FISIP UNS Research Group, in collaboration with Sanggar Permadani. The method used was participatory and educational, including lectures, discussions, and hands-on practice with the physical items integrated into the fashion training. The training revealed an increase in participants' understanding, interest, and motivation toward preserving traditional Javanese clothing. On a more abstract level, it is recognized that collective awareness of clothing as a form of identity is continuously being built, although without proper motivation, this effort may face greater challenges.